MiR-3120 Is a Mirror MicroRNA That Targets Heat Shock Cognate Protein 70 and Auxilin Messenger RNAs and Regulates Clathrin Vesicle Uncoating - Scott, Helen (American Society for Biochemistry and Molecular Biology, 2012)
We show that a single gene locus gives rise to two fully processed and functional miRNAs, i.e. that due to imperfect base pairing, two distinct microRNAs (miRNAs) can be produced from the fully complementary DNA strands. The antisense strand encodes miR-214, which is transcribed by its own promoter, whereas a novel miRNA, miR-3120, is co-expressed with its host gene mRNA. We also found that miR-3120 regulates important aspects of cellular function that are similar to that of its host gene, dynamin-3. miR-3120 was found to be located in neuronal cell bodies and to target Hsc70 and auxilin, and its lentivirus-mediated expression inhibited the uncoating of clathrin-coated vesicles. Finally, mirror miRNAs are likely to represent a new group of miRNAs with complex roles in coordinating gene expression.